Nonsurgical Orthodontic Airway Plate Treatment for Newborns With Robin Sequence. (March 2022) - Choo, HyeRan; Khosla, Rohit K.; Meister, Kara D.; Wan, Derrick C.; Lin, Hung-Fu C.; Feczko, Robert; Bruckman, Karl; Hopkins, Elena; Truong, Mai Thy; Lorenz, Hermann P.
Despite promising outcomes for >50 years, nonsurgical orthodontic airway plates (OAP) are only infrequently offered for babies with Robin sequence in a few parts of the world. This article demonstrates possibility of providing functional improvement using an OAP to help these babies overcome their functional and structural difficulties on their own. Two consecutively treated cases are presented exemplifying that OAP treatment that had originated from Europe is reproducible and effective in an institution in the United States.